Cross-sensitization between testosterone and cocaine in adolescent and adult rats - Engi, Sheila A. [UNESP]; Cruz, Fabio C. [UNESP]; Crestani, Carlos C. [UNESP]; Planeta, Cleopatra da Silva [UNESP] (Elsevier B. V., 2015)
Cocaine and anabolic-androgenic steroids are substances commonly co-abused. The use of anabolic steroids and cocaine has increased among adolescents. However, few studies investigated the consequences of the interaction between anabolic-androgenic steroids in animals' model of adolescence. We examined the effects of acute and repeated testosterone administration on cocaine-induced locomotor activity in adult and adolescent rats. Rats received ten once-daily subcutaneous (s.c.) injections of testosterone (10mg/kg) or vehicle. Three days after the last testosterone or vehicle injections rats received an intraperitoneal (i.p.) challenge injection of either saline or cocaine (10mg/kg). A different subset of rats was treated with a single injection of testosterone (10mg/kg) or vehicle and three days later was challenged with cocaine (10mg/kg, i.p.) or saline. Immediately after cocaine or saline injections the locomotor activity was recorded during forty minutes. Our results demonstrated that repeated testosterone induced locomotor sensitization to cocaine in adolescent but not adult rats.
Keywords: Adolescent; Adult; Behavioral sensitization; Cocaine; Rats; Testosterone